دور منظمة أوبك في سوق النفط الدولية و آفاقها المستقبلية - أحمد, محسن إبراهيم (Sulaimani Journal for Humanities, 2001)
OPEC is one of the important economical organizations of the developing countries in particular and world states in general. The importance of this organization goes back to possessing the highest rate of safe oil , which is a strategic power ; it was and is still the main reason behind many of the international struggles and disputes , since it is at the top of the energy sources , inspite of all the attempts that were and are made especially by the international energy company after the first oil crisis in 1973 for the sake of decresing dependence on oil as the main source of energy . In addition , oil and it's derivations contribute in producing more than seven handred industrial substances despit it's importance in the political and stratigic aspectes .It is expected that the role of OPEC in the international oil market will develop in the futuer as the result of the international increase in oil demand on the one hand , and the decrease of the role of oil producing countries outside OPEC in the oil market because of the end of it's safe oil on the other hand.